2015
DOI: 10.1186/s13041-015-0109-y
|View full text |Cite|
|
Sign up to set email alerts
|

Networked neural spheroid by neuro-bundle mimicking nervous system created by topology effect

Abstract: In most animals, the nervous system consists of the central nervous system (CNS) and the peripheral nervous system (PNS), the latter of which connects the CNS to all parts of the body. Damage and/or malfunction of the nervous system causes serious pathologies, including neurodegenerative disorders, spinal cord injury, and Alzheimer’s disease. Thus, not surprising, considerable research effort, both in vivo and in vitro, has been devoted to studying the nervous system and signal transmission through it. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…[105] In another study, Jeong et al reported an improved model of neurospheroids cultured in PDMS microwells. [146] They used deep hemi-cylindrical channels well networked to enhance the formation of neurospheroids that release laminin and induce higher differentiation of the neural progenitor cells into glia and neurons. They also showed electrical activity likely due to the networks formed between the neurospheroids.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…[105] In another study, Jeong et al reported an improved model of neurospheroids cultured in PDMS microwells. [146] They used deep hemi-cylindrical channels well networked to enhance the formation of neurospheroids that release laminin and induce higher differentiation of the neural progenitor cells into glia and neurons. They also showed electrical activity likely due to the networks formed between the neurospheroids.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%
“…They also showed electrical activity likely due to the networks formed between the neurospheroids. [146] …”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%
“…Adding Aβ tot eh network resulted in decreased cell viability and neurite degeneration. A similar neurospehere network produced by Jeong et al 136 to study signal transmission through the CNSas a result of the partial breakdown in this system seen in Alzheimer's disease. Shallow (70µm) and deep (300µm) hemicylindrical channel networks between concave wells seeded with neural progenitor cells formed a self-aggregating network, Figure 2B.…”
Section: Networked Neurospheresmentioning
confidence: 99%
“…Axonal signalling was recorded being transmitted between the spheroids, detected by Ca 2+ flux imaging. 136 Further models are summarised and reviewed in. 137,138 An important consideration when designing an in vitro model of the brain is interstitial fluid flow.…”
Section: Networked Neurospheresmentioning
confidence: 99%
“…Central nervous system (CNS) CNS axons, 63 neuronal networks, 22,23,28 cortical cell layers, 24 miro-bloodbrain barrier (BBB), 26 BBB (neurovascular unit) 25 neurovascular unit, 38 brain barriers (blood-brain, brain-CSF, and blood-CSF Blood brain barrier). 39…”
mentioning
confidence: 99%